Evaluation of a new chemical nematicide, fluazaindolizine (ReklemelTM active), for plant-parasitic nematode management in bermudagrass - Groover, Will L.; Lawrence, Kathy S. (Journal of nematology, 2021)
Plant-parasitic nematodes are a major pest of turfgrass in the United States, yet there are few options for successful management. Most current management strategies rely on the use of a limited number of chemical nematicides, so finding a new management option for nematode suppression would be extremely valuable for turfgrass managers. The aim of this study is to evaluate a new nematicide, fluazaindolizine (Reklemel™ active), for its ability to reduce plant-parasitic nematode population density and improve turfgrass quality. Separate research trials were conducted on bermudagrass infested with and in greenhouse, microplot, and field settings over 2018 and 2019. Both greenhouse evaluations demonstrated multiple rates of fluazaindolizine reduced population density, and one of the two trials showed multiple rates of fluazaindolizine reduced nematode population density. Fluazaindolizine was also effective at reducing population density of both and in microplot settings for both 2018 and 2019, and a significant improvement in turf quality was observed for both visual turfgrass ratings and NDVI. Field trials demonstrated a significant reduction for both and population density by multiple rates of fluazaindolizine, but no significant differences in turf quality ratings were observed. Overall, fluazaindolizine shows promise as a chemical nematicide for plant-parasitic nematode management on turfgrass.